Comparative performance reports in anaesthesia: impact on clinical outcomes and acceptability to clinicians. Issue 3 (21st July 2018) - Collyer, Thomas; Robertson, Martyn; Lawton, Thomas; Rothwell, Alice
Abstract : In anaesthesia, the use of comparative performance reports, their impact on patient care and their acceptability is yet to be fully clarified. Since April 2010, postoperative data on theatre cases in our trust have been analysed and individual comparative performance reports distributed to anaesthetists. Our primary aim was to investigate whether this process was associated with improvement in overall patient care. A short survey was used to assess our secondary aim, the usefulness and acceptability of the process. There were significant improvements in the odds of all outcomes other than vomiting: 39% improvement in hypothermia (p<0.001); 9.9% improvement in severe pain (p<0.001%); 9.6% improvement in moderate pain (p<0.001); 5.3% improvement in percentage pain free (p=0.04); 9.7% improvement in nausea (p=0.02); 30% improvement in unexpected admissions (p=0.001). 100% of consultant respondents agreed that performance reports prompted reflective practice and that this process had the potential to improve patient care. The provision of comparative performance reports was thus associated with an improvement in outcomes while remaining acceptable to the anaesthetists involved.